Analysis of the Genetic Diversity of Two Rhopalosiphum Species from China and Europe Based on Nuclear and Mitochondrial Genes - Jianqing Guo; Jing Li; Sebastien Massart; Kanglai He; Frédéric Francis; Zhenying Wang (Insects, 2023)
Population genetic studies can reveal clues about the evolution of adaptive strategies of aphid species in agroecosystems and demonstrate the influence of environmental factors on the genetic diversity and gene flow among aphid populations. To investigate the genetic diversity of two Rhopalosiphum aphid species from different geographical regions, 32 populations (n = 535) of the bird cherry-oat aphid (Rhopalosiphum padi Linnaeus) and 38 populations (n = 808) of the corn leaf aphid (Rhopalosiphum maidis Fitch) from China and Europe were analyzed using one nuclear (elongation factor-1 alpha) and two mitochondrial (cytochrome oxidase I and II) genes. Based on the COI-COII sequencing, two obvious clades between Chinese and European populations and a low level of gene flow (Nm = 0.15) were detected in R. padi, while no geographical-associated genetic variation was found for EF-1α in this species. All genes in R. maidis had low genetic variation, indicating a high level of gene flow (Nm = 5.31 of COI-COII and Nm = 2.89 of EF-1α). Based on the mitochondrial result of R. padi, we concluded that the long distance between China and Europe may be interrupting the gene flow. The discordant results of nuclear gene analyses in R. padi may be due to the slower evolution of nuclear genes compared to mitochondrial genes. The gene exchange may occur gradually with the potential for continuous migration of the aphid. This study facilitates the design of control strategies for these pests.